(untitled) (Alternate Horizons, 2021)
Globally, democracy is on the decline, threatening the achievability of the landmark Agenda 2030 Sustainable Development Goals. Digital technologies have enabled new covert competitive authoritarian tactics. Renewed surveillance laws and public and international awareness of these tactics is required to regain the global democratic rights and civil liberties required for Agenda 2030.